2016
DOI: 10.4317/jced.52803
|View full text |Cite
|
Sign up to set email alerts
|

"Osteolipoma of buccal mucosa: Case report and literature review"

Abstract: Osteolipoma affecting oral cavity is indeed rare. We hereby report a case of osteolipoma affecting buccal mucosa. A review of literature of osteolipoma of oral cavity, particularly on radiographic/imaging findings was done. Only 16 cases of Osteolipoma of oral cavity are reported in the literature. The radiographic findings of our case, i.e. multiple dense homogenous radio-opaque structures was reported earlier only in one case [out of 16] of osteolipoma of oral cavity. Key words:Lipoma, osteolipoma, panoram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…OPG and periapical intraoral radiograph are the cost-effective and simple radiographs which can aid in the diagnosis. A total of two cases[23] have been documented in literature (5.88%) with “multiple dense homogeneous radiopaque structures” similar to our case [Figure 4]. …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…OPG and periapical intraoral radiograph are the cost-effective and simple radiographs which can aid in the diagnosis. A total of two cases[23] have been documented in literature (5.88%) with “multiple dense homogeneous radiopaque structures” similar to our case [Figure 4]. …”
Section: Discussionsupporting
confidence: 67%
“…[12] However, in our case, the trabeculae were distributed equally in a uniform manner throughout the tumor-like “concentric layers.”…”
Section: Discussionmentioning
confidence: 85%
“…Histologically, oral lipomas are divided into subtypes based on the matrix and the properties of tumor cells: simple lipoma, fibrolipoma 4,12,13 , spindle cell lipoma 5,14 , intramuscular lipoma 14 , chondrolipoma, pleiomorphic lipoma, myxoid lipoma or myxolipoma 15 , angiolipoma 16,17 , osteolipoma 18,19 , angiomyxolipoma, sialolipoma, infiltrating lipoma, perineural lipoma, intraneural lipoma and atypical lipoma 1,2,8 . Despite the fact that the etiology and pathogenesis of the tumor are not clear, two main theories have been claimed: (i) The Hypertrophy theory, which correlates obesity and inadvertent growth of adipose tissue with the formation of oral lipoma 1 .…”
Section: Discussionmentioning
confidence: 99%
“…peripheral giant cell granuloma, fibroma, pyogenic granuloma etc. (7,16,48) Fregnani et al (49) in their study of 46 cases found most of the cases affected adults with no gender predilection. Intra orally they found buccal mucosa as the most involved site followed by tongue, lips and floor of mouth.…”
Section: Resultsmentioning
confidence: 99%
“…(Table 3). (1,3,7,14,15,16,21,47,48) Clinically most of the lipomas presented as a soft tissue painless growth, irrespective of their histological diagnosis and they often masquerade other common neoplastic and reactive growths of oral cavity i.e. peripheral giant cell granuloma, fibroma, pyogenic granuloma etc.…”
Section: Resultsmentioning
confidence: 99%